2006
DOI: 10.1002/chin.200613216
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 4,6,3′,4′‐Tetrasubstituted Aurones via Aluminium Oxide‐Catalyzed Condensation.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Reaction of compound 2 with methyl iodide in a molar ratio 1:317, 18 at 0 °C to room temperature gave a mixture of dimethoxy product 3 and unexpected product 4 . Compound 3 cannot be transformed to 4 in the presence of potassium carbonate and methyl iodide.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Reaction of compound 2 with methyl iodide in a molar ratio 1:317, 18 at 0 °C to room temperature gave a mixture of dimethoxy product 3 and unexpected product 4 . Compound 3 cannot be transformed to 4 in the presence of potassium carbonate and methyl iodide.…”
Section: Resultssupporting
confidence: 87%
“…According to the literature,18 the iminium salt 1 was hydrolysed with aqueous hydrochloric acid to provide a mixture of benzofuranone 2 and 2′,4′,6′‐trihydroxy‐2‐chloroacetophenone; the mixture was treated with sodium methoxide to produce 2 . In the experiments it was found that the iminium salt 1 can directly be transformed in 77.3% yield to 2 in refluxing water, and the product can be used as starting material without any further purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the reported aurone derivatives having similar structural features (Bolek and Gutschow, 2005;Detsi et al, 2009;Seabra et al, 1997;Venkateswarlu et al, 2004). The Z-configuration was defined according to the chemical shift values of (C-10) of the exocyclic olefinic (=C-H) carbon (Fig.…”
Section: Nmr Spectroscopysupporting
confidence: 58%
“…The protection of the hydroxyl group of 13a with MOMCl produced compound 13c with a 58% yield. The aldol condensation reaction, which is a key reaction in this process, of 13b , c with aromatic aldehydes 5a – f in the presence of aluminum oxide produced the corresponding aurones 14a – l with 31–89% yields [ 6 ]. In this reaction, the use of 13a resulted in decreasing yields.…”
Section: Resultsmentioning
confidence: 99%